Ergonomic Risk Factors Evaluation of Work-related Musculoskeletal Disorders by PATH and MMH in a Construction Industry - Morteza Cheraghi; Meysam Shahrabi-Farahani; Seyyed Ali Moussavi-Najarkola (Iranian Journal of Health, Safety and Environment, 2019)
One of the prevalent injurious factors and disabilities is work-related musculoskeletal disorders (WMSDs). The aim of this study is to evaluate the risks of ergonomic factors inducing musculoskeletal disorders consequent from industrial construction by means of PATH (Posture, Activity, Tools and Handling) risk evaluation and MMH (Manual Material Handling). A cross-sectional study was conducted on 357 construction workers working in 21 different jobs of construction industry in Parand New City, south-west of Tehran, Iran. Nordic musculoskeletal questionnaire (NMQ) was used to determine the prevalence of musculoskeletal disorders. PATH was served to assess different body part postures such as back, feet, hands, also weight of tools and equipment and catching by hand (hand-catch). Most prevalence of musculoskeletal disorders was around back (30.5%) and knee (28.9%), and in opposed side elbow (4.2%) respectively. The results of Nordic musculoskeletal questionnaire (NMQ) showed that there is meaningful relation through pain of neck, wrist, hand, back and knee with workers age and working experience (P